Effects of Replacing Fishmeal with Defatted Black Soldier Fly (Hermetia illucens Linnaeus) Larvae Meal in Japanese Eel (Anguilla japonica) Diet on Growth Performance, Fillet Texture, Serum Biochemical Parameters, and Intestinal Histomorphology - I-Pei Kuo; Ching-Shuo Liu; Shuenn-Der Yang; Shih-Hsiang Liang; Yeh-Fang Hu; Fan-Hua Nan (Aquaculture Nutrition)
An 8-week feeding trial was conducted to investigate the effects of replacing fishmeal with defatted black soldier fly larvae meal (DBSFLM) in the diets of Japanese eel on their growth performance, fillet texture, serum biochemical parameters, and intestinal histomorphology. Six isoproteic (520 g kg−1), isolipidic (80 g kg−1), and isoenergetic (15 MJ kg−1) diets were formulated with fishmeal replacement levels of 0% (R0), 15% (R15), 30% (R30), 45% (R45), 60% (R60), and 75% (R75). The growth performance, feed utilization efficiency, survival rate, serum liver function enzymes, antioxidant ability, and lysozyme activity of fish were not affected (P>0.05) by DBSFLM. However, the crude protein and cohesiveness of the fillet in groups R60 and R75 significantly decreased, and the fillet hardness significantly increased (P<0.05). Additionally, the intestinal villus length significantly decreased in the R75 group, and the goblet cell densities were significantly lower in the R45, R60, and R75 groups (P<0.05). Overall, high levels of DBSFLM did not affect growth performance and serum biochemical parameters but significantly altered fillet proximate composition and texture and intestinal histomorphology (P<0.05). The optimal fishmeal replacement level is 30% with 184 g kg−1 DBSFLM.